EVALUASI LANDASAN ILMU PENGETAHUAN DALAM PENGEMBANGAN KURIKULUM BERBASIS KOMPETENSI PADA PENDIDIKAN DASAR - Andriani, Yuli; Effy Mulyasari; Deri Hendriawan; Eti Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The competency-based curriculum represents an educational framework that aims to foster students understanding, abilities, and values in a holistic manner. Creating such a curriculum relies heavily on scientific principles that provide the foundation for establishing learning goals, subject matter, instructional strategies, and evaluation techniques. This investigation seeks to examine how scientific principles contribute to designing a competency-based curriculum for primary education. The study uses a library research approach by examining and interpreting related materials such as books, scholarly articles, curriculum frameworks, and educational regulations. The results demonstrate that scientific principles are vital in maintaining curriculum content that aligns with developments in science, technology, and societal demands. They also aid in cultivating analytical thinking, problem-solving capabilities, and continuous that aligns with developments in science, technology, and societal demands. learning among learners. Nevertheless, incorporating scientific principles into curriculum design presents various obstacles, such as the disconnect between theoretical ideas and actual teaching methods, insufficient teacher expertise, and the swift rate of scientific and technological advancements. Consequently, ongoing curriculum assessment and refinement are required to preserve its appropriateness and success in accomplishing educational objectives. The study determines that reinforcing scientific principles is crucial for improving the quality of competency-based curriculum execution in primary education.